Big Learning Data - Masie, Elliott (Association for Talent Development, 2013)
In today's wired world, we interact with millions of pieces of information every day. Capturing that information and making sense of it is the revolutionary impact of big data on business-and on learning. Thought leader Elliott Masie and Learning CONSORTIUM Members bring a powerful new book to the T & D profession. They provide a SWOT analysis of big data and implications for learning and development professionals. Big learning data is at your fingertips. You need to know why it matters. Find out where to start with big learning data. Think differently about the data you have. Understand the risks that come with big data. Solve problems using the new perspectives and measurement support that big learning data provides.